Healthcare indicators associated with COVID-19 death rates in the European Union. (April 2021) - Mattiuzzi, C.; Lippi, G.; Henry, B.M.
Abstract: Objectives: Identification of environmental and hospital indicators that may influence coronavirus disease 2019 (COVID-19) mortality in different countries is essential for better management of this infectious disease. Study design: Correlation analysis between healthcare system indicators and COVID-19 mortality rate in Europe. Methods: For each country in the European Union (EU), the date of the first diagnosed case and the crude death rate for COVID-19 were retrieved from the John Hopkins University website. These data were then combined with environmental, hospital and clinical indicators extracted from the European Health Information Gateway of the World Health Organization. Results: The COVID-19 death rate in EU countries (mean 1.9 ± 0.8%) was inversely associated with the number of available general hospitals, physicians and nurses. Significant positive associations were also found with the rate of acute care bed occupancy, as well as with the proportion of population who were aged older than 65 years, overweight or who had cancer. Total healthcare expenditure, public sector health expenditure and the number of hospital and acute care beds did not influence COVID-19 death rate. Conclusions: Some common healthcare system inadequacies, such as limited numbers of general hospitals, physicians and nurses, in addition to high acute care bed occupancy, may be significant drivers of nationwide COVID-19 mortality rates in EU countries. Article in a Tweet: Coronavirus disease 2019 (COVID-19) mortality in European Union countries is inversely associated with the number of general hospitals, physicians and nurses. Positive associations were found between COVID-9 mortality and acute care bed occupancy. Populations with high numbers of individuals who were aged >65 years, who were overweight or who had cancer showed increased COVID-19 mortality rates. Total healthcare expenditure, public sector health expenditure and the number of hospital and acute care beds did not influence COVID-19 mortality.